The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/corg.12073
|View full text |Cite
|
Sign up to set email alerts
|

Mediation or Moderation? The Role of R&D Investment in the Relationship between Corporate Governance and Firm Performance: Empirical Evidence from the Chinese IT Industry

Abstract: Manuscript Type: EmpiricalResearch Question/Issue: This paper explores whether R&D investment has a mediating and/or moderating effect on the relationship between corporate governance and firm performance. Research Findings/Insights: This empirical study of Chinese IT-industry listed companies during the 2007-2008 period shows that R&D investment does not moderate, but instead mediates the relationship between corporate governance and firm performance. Theoretical/Academic Implications: This paper takes the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 131 publications
1
36
0
2
Order By: Relevance
“…However, studies carried out by Cowling [25] and Hottenrott et al [26] show that RDFS positively influence R&D investment, which can significantly increase the R&D output of SMEs. In this context, we put forward the hypothesis 6 and the testing results proved that RRDI indeed mediates the relationship between RDFS and the sustainable patent output of SMEs, which is similar to Zhang et al [50], who suggested that R&D investment mediated the relationship between corporate governance and firm performance.…”
Section: Discussion Of the Findingssupporting
confidence: 74%
“…However, studies carried out by Cowling [25] and Hottenrott et al [26] show that RDFS positively influence R&D investment, which can significantly increase the R&D output of SMEs. In this context, we put forward the hypothesis 6 and the testing results proved that RRDI indeed mediates the relationship between RDFS and the sustainable patent output of SMEs, which is similar to Zhang et al [50], who suggested that R&D investment mediated the relationship between corporate governance and firm performance.…”
Section: Discussion Of the Findingssupporting
confidence: 74%
“…5 Table 1 also reports the descriptive statistics of the various variables used in our regressions. Our set of control variables consists of the well-known determinants of innovation, including return on assets (ROA), Tobin's Q, CEO tenure, capital expenditure ratio, tangibility, financial constraints (Kaplan and Zingales, 1997), institutional ownership (Choi, Park and Hong, 2012), leverage (Zhang, Chen and Feng, 2014), total assets and financial analysts' coverage (He and Tian, 2013). A detailed definition of these variables is provided in the Appendix and their correlation matrix is reported in Table 2.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…At first we considered the time lag effect of R&D investments on financial performance. As documented by Parcharidis and Varsakelis (2010), Mezghanni (2011) and Zhang et al (2014), R&D investments are long-term projects and so they take time to prosper and produce positive results on corporate performance and profitability. Thus, following the above mentioned studies both models were re-estimated using 1 and 2 year lags of the R&D investments and expenses variables.…”
Section: Resultsmentioning
confidence: 99%